Wi-Fi fingerprint similarity in collaborative radio maps for indoor positioning - Matos, Diogo André da Silva (2014)
Positioning systems based on Wi-Fi fingerprinting has become very popular in recent years. These systems have been attracting the attention of many researchers and companies because they provide a low cost solution for real time positioning of both people and objects. However, the construction of radio map that supports these solutions remain a challenge in both indoor and outdoor environments. This paper discusses the potential of engaging users of mobile applications for social networks in the collaborative construction of ra- dio maps. Particularly, it describes a solution to improve the users’ experience when moving to unmapped areas. Some experimental results are presented to assess the proposed solution.